Misunderstanding and Offense in the Digital World as Impacts of Community Low Level of Language Literacy and Communication Skills - Herman Resyadi (Palakka : Media and Islamic Communication, 2022)
AbstractCommunication is part of social interaction that acts as a means of exchanging information, meeting individual needs and development. However, such social interaction activities may fail and create interaction problems, including misunderstanding and offense. Misunderstanding occurs when the listener thinks he or she has understood or misinterpreted what the speaker meant while offense occurs when the listener is unable to accept, is annoyed and disturbed by what the speaker is saying. Since entering the digital era which began about 10 years ago, misunderstandings and offenses have become increasingly common. The rapid flow of information exchange where everyone is almost free to speak and respond to speech makes these two issues even more unstoppable. Responding to these, as the main concern of this paper, the author invites the readers to discuss about misunderstanding and offense as results of individual low level of literacy and communication skills.Keywords: Misunderstanding and Offense, Communication, Language Literacy